Being wheelchair‐bound and being bedridden: Two concept analyses - Johannes Schirghuber; Berta Schrems (Wiley, 2023)
Abstract Aim Analysis of the concepts and development of a conceptual definition of being wheelchair‐bound and being bedridden. Design Concept analysis. Methods Walker and Avant´s concept analysis method was used. A thematic analysis guided the determination of the attributes, antecedents and consequences. Results Being wheelchair‐bound and being bedridden are defined as permanent states in which people are bound to an object. Being passively bound to a wheelchair and being bedridden both mean an increasing restriction of the life‐space. Being passive wheelchair‐bound often represents a preliminary stage to being bedridden. Both concepts have six attributes: in need of help, powerlessness, life‐space confinement, mobility limitation, endurance and weakness. They differ in the main feature maintaining an independent sitting position. Physical immobility and physiological instability are antecedents with the following influencing factors: illness, complexity, burden, endogenous/exogenous booster. The consequences are the progression of inactivity and all related physical and psycho‐social problems.